Online population control surveys: A new method for investigating foodborne outbreaks. (2020) - Taylor, M.; Galanis, E.
Abstract: In foodborne outbreak investigations, case-control and cohort studies are used to test hypotheses and identify a source, but these studies are resource-intensive and may have challenges of representativeness, temporality or accessibility. We used online surveys to collect population control data for two foodborne outbreaks and compared the data collected to our cases and existing population exposure data. Online survey population controls were comparable to cases based on age and sex. Exposure data collected through online surveys were more precise than existing control data, represented the disease-specific exposure period and could be easily modified. In one outbreak the online control exposure data differed from established population data. In both outbreaks, the information from the online population control survey supported the hypothesis of the investigation. Our findings demonstrate that online surveys were a rapid and representative way to collect responses from controls during outbreak investigations.